The Effect of Husk Charcoal as Planting Media on Seed Potato Cultivation (Solanum Tuberosum L.) of Granola Group G0 Varieties - Purba, Jarinsen Yanardo; Setiyo, Yohanes; Sumiyati , Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Seeds are an important factor in the success of planting potatoes. In Indonesia, the availability of quality potato seeds is very small. The aims of this research were (1) to find out the best composition of the rice husk charcoal and soil planting medium in terms of the physical properties of the planting medium and (2) to find out the best media capable of optimally producing seed potatoes with the best quality. This study used a factorial design with two factors. The first factor is the composition of the planting medium which consists of 5 levels, the second factor is the observation time which consists of 4 levels. Five levels of cultivation treatment consisted of husk charcoal and soil, four levels of observation were 2 weeks, 4 weeks, 6 weeks and 8 weeks. husk charcoal 100%, soil 100%, husk charcoal: 50% soil: 50%, husk charcoal: 75% soil: 25%, and husk charcoal: 25% soil: 75%. The parameters observed in this study included the porosity of the planting medium, pH and electrical conductivity of nutrients, volume of nutrients bound to the growing media, plant development and productivity. Judging from the physical properties, the results showed that the media of 100% husk charcoal had the best porosity of 55.35%, and a pH value of 6.7. Husk charcoal: 50% soil: 50% yields water availability for plants 22.04% w.b, has the highest binding of nutrients with a value of 742 µS/cm, plant height 74 cm, maximum number of leaves 14 leaf branches, root length down 63 cm, and the average number of tubers is at most 7 knol/plant. Treatment of rice husk charcoal: soil 50% : 50% was the best capable of producing potato seeds by producing a tuber weight of 240 g/plant and producing 29 S and M sized tubers from 40 tubers.